2018
DOI: 10.3390/ijerph15071420
|View full text |Cite
|
Sign up to set email alerts
|

A Cost-Benefit Analysis of the Official Development Assistance Project on Maternal and Child Health in Kwango, DR Congo

Abstract: A project on maternal and child health (MCH) was conducted by the Korea International Cooperation Agency to reduce maternal and child mortality rates in Kwango, Democratic Republic of Congo (DRC). The objective of this study was to evaluate the costs and benefits of the MCH project, which was under Official Development Assistance for a period of 3 years from 2014 to 2016. The study conducted a cost-benefit analysis (CBA) using a benefit-cost ratio (BCR). The costs were the total costs incurred in implementing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The analysis suggested that higher per capita aid for education significantly increases primary school enrollment, while increased domestic government spending on education does not. Shirazi et al (2010) suggested that the causal effects of aid and economic growth are positive impacts on education, life expectancy, and human development [35][36][37]. The results of Ranis et al (2000) were also similar.…”
Section: Oda Effectivenessmentioning
confidence: 87%
See 2 more Smart Citations
“…The analysis suggested that higher per capita aid for education significantly increases primary school enrollment, while increased domestic government spending on education does not. Shirazi et al (2010) suggested that the causal effects of aid and economic growth are positive impacts on education, life expectancy, and human development [35][36][37]. The results of Ranis et al (2000) were also similar.…”
Section: Oda Effectivenessmentioning
confidence: 87%
“…Most research has been largely based on case studies [37] of specific donor countries, but such studies have not conducted much specific statistical analysis, such as the types of aid program individually, to verify the determinants of aid concentration. Previous research has neglected the fact that sector-specific aid can be more effective than total aid with ineffective sub-aid programs and, furthermore, that each developing country has a unique combination of various sub-programs in ODA.…”
Section: Oda Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…KOICA funded Yonsei Global Health Center (YGHC) to implement and evaluate this MCH project. YGHC, in a previous study, calculated the cost-benefit ratio (BCR) of this MCH project at 3.41, which means that the project was “more than 3 times more likely to provide benefits than cost” [15]. Although this project calculated the BCR, the impact of the MCH intervention project on the ANC service utilization by the reproductive-aged women in the DRC remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the government should strive to lower fees for outpatient care to encourage citizens to visit when sick before their conditions deteriorate. Some developing countries have conducted a cost benefit analysis of their healthcare [36]. A study by Muriithi [37] found out that user fees was among the key determinants of whether a patient is treated or not.…”
Section: Discussionmentioning
confidence: 99%